2017
DOI: 10.1007/s00383-017-4181-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laminin-1 on enteric neural crest-derived cell migration in the Hirschsprung’s disease mouse model

Abstract: Our results suggest that laminin-1 does not have a positive effect on ENCC migration in HD mice on E12.5, in contrast to the phenomenon seen in normal mice gut specimens, where laminin-1 promotes ENCC migration during the same period. This suggests that there is an impairment in the interaction between ENCC and extracellular environmental factors, which are required for normal development of the enteric nervous system, resulting in an aganglionic colon in HD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…We have previously demonstrated that β1 integrin expression was speci cally decreased in ENCC in Ednrb KO mice but not in the gut during this crucial period [10]. Moreover, it has been reported that expression of laminin, which is the ligand of β1 integrin and promotes neurite outgrowth, is increased in aganlionic colon in human and this model [11,12].…”
Section: Discussionmentioning
confidence: 75%
“…We have previously demonstrated that β1 integrin expression was speci cally decreased in ENCC in Ednrb KO mice but not in the gut during this crucial period [10]. Moreover, it has been reported that expression of laminin, which is the ligand of β1 integrin and promotes neurite outgrowth, is increased in aganlionic colon in human and this model [11,12].…”
Section: Discussionmentioning
confidence: 75%
“…Aberrant expression of ECM proteins in aganglionic segments has been demonstrated associated with HSCR phenotypes such as ENCC development and migration. 5,6,13,15,[20][21][22][23] In addition, previous studies have found abnormal expression of ECM proteins 7,58 and fibrotic regulators in intestinal fibrosis, and myofibroblast activation is also an essential manifestation of intestinal fibrosis. 49,50,59 Here, we provide evidence in HSCR that there is a fibrotic phenotype in aganglionic segments by comprehensively exploring the heterogeneity of the ECM-related stromal cells and glial cells in the HSCR segment.…”
Section: Discussionmentioning
confidence: 99%
“… 4 ECM dysregulation affects ENCC colonisation and survival. 5 , 6 Moreover, abnormal ECM is associated with intestinal fibrosis in intestinal inflammation such as enterocolitis. 7 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations